Validation of a suspension model and its elastic behaviour demonstrated at the formula student race car of the University Duisburg-Essen / Frédéric Etienne Kracht ... [et al.] - Frédéric, Etienne Kracht; Alex Armando, Roempler Dellien; Dieter, Schramm (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Various types of models have been used for many years to predict the motion of vehicle chassis. The complexity of these models ranges from rather basic to sophisticated models including the elasticity of selected components. For the latter flexible multibody models can be used to model in detail the elasto-kinematic behaviour of a vehicle suspension system by modelling components as FE bodies. However, a model can only be considered valid after a successful validation process. Standardized tests like the wheel travel test and the doublelane change manoeuvres are suitable for this purpose. It is not trivial to measure the kinematics due to the dynamic elastic deformations of the parts. This paper demonstrates how to assess the significance of such effects on the kinematics. Laser sensors are used to measure the time-dependent position of the parts. Stress gauges are also used to record stress and strain data of the metallic parts. Acceleration sensors are then applied to calculate the influence of the moving chassis. All measurements are taken from the double-wishbone suspension equipped formula student race car. For the validation of the models, experimentally measured data is compared against simulation data. Differences are minimized using optimization tools. Acceptable agreement between measured data and simulation data were obtained. The result is that non-meas- ured manoeuvres can also be simulated using the validated model thereon af- ter.